Root Nodule Rhizobia From Undomesticated Shrubs of the Dry Woodlands of Southern Africa Can Nodulate Angolan Teak Pterocarpus angolensis, an Important Source of Timber - Bünger, Wiebke; Sarkar, Abhijit; Grönemeyer, Jann Lasse; Zielinski, Janina; Revermann, Rasmus; Hurek, Thomas; Reinhold-Hurek, Barbara (Frontiers in Microbiology, 2021)
Pterocarpus angolensis, a leguminous tree native to the dry woodlands of Southern Africa, provides valuable timber, but is threatened by land conversion and overharvesting while showing limited natural regeneration. Nitrogen-fixing root nodule symbionts that could improve establishment of young seedlings have not yet been described. Therefore, we investigated the ability of P. angolensis to form nodules with a diverse range of rhizobia. In drought-prone areas under climate change with higher temperatures, inoculants that are heat-tolerant and adapted to these conditions are likely to be of advantage. Sources of bacterial isolates were roots of P. angolensis from nurseries in the Kavango region, other shrubs from this area growing near Pterocarpus such as Indigofera rautanenii, Desmodium barbatum, Chamaecrista sp., or shrubs from drought-prone areas in Namaqualand (Wiborgia monoptera, Leobordea digitata) or Kalahari (Indigofera alternans). Only slight protrusions were observed on P. angolensis roots, from which a non-nodulating Microbacterium sp. was isolated. Rhizobia that were isolated from nodules of other shrubs were affiliated to Bradyrhizobium ripae WR4T, Bradyrhizobium spp. (WR23/WR74/WR93/WR96), or Ensifer/Mesorhizobium (WR41/WR52). As many plant growth-promoting rhizobacteria (PGPR), nodule isolates produced siderophores and solubilized phosphate. Among them, only the Bradyrhizobium strains nodulated P. angolensis under controlled conditions in the laboratory. Isolates were further characterized by multilocus sequence analysis and were found to be distant from known Bradyrhizobium species. Among additional reference species tested for nodulation on P. angolensis, Bradyrhizobium vignae 7-2T and Bradyrhizobium namibiense 5-10T from the Kavango region of Namibia as well as Bradyrhizobium elkanii LMG6234T and Bradyrhizobium yuanmingense LMG21728T induced nitrogen-fixing nodules, while Bradyrhizobium diazoefficiens USDA110T and Bradyrhizobium tropiciagri SEMIA6148T did not. This suggests a broad microsymbiont range from Bradyrhizobium japonicum and B. elkanii lineages. Phylogenetic analysis of nodC genes indicated that nodulating bradyrhizobia did not belong to a specific symbiovar. Also, for I. rautanenii and Wiborgia, nodule isolates B. ripae WR4T or Mesorhizobium sp. WR52, respectively, were authenticated. Characterization of symbionts inducing effective root nodules in P. angolensis and other shrubs from Subsahara Africa (SSA) give insights in their symbiotic partners for the first time and might help in future to develop bioinoculants for young seedlings in nurseries, and for reforestation efforts in Southern Africa.